The short-run effect of monetary policy shocks on credit risk: An analysis of the euro area - Chi Hyun Kim; Lars Other (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We examine the credit channel of monetary policy from 2000 to 2015 in the Euro Area using daily monetary policy shock and credit risk measures in an autoregressive distributed lag model. We find that an expansionary monetary policy shock leads to a short-run increase in the credit risk of non-financial corporations. This dysfunctionality of the credit channel is driven by the crisis-dominated post-2009 period. During this period, market participants may have interpreted expansionary monetary policy shocks as a signal of worsening economic prospects. We further distinguish policy shocks aiming at short- and long-run expectations of market participants, i.e. target and path shocks. The adverse effect disappears for crisis countries when the European Central Bank targets long-run rather than short-run expectations.
Keywords: C22; E44; E52; G12; 330; Credit Channel; Credit Spreads; Euro Area Financial Markets; Forward Guidance; Monetary Policy; Zero Lower Bound